Slight Disruption in Intestinal Environment by Dextran Sodium Sulfate Reduces Egg Yolk Size Through Disfunction of Ovarian Follicle Growth - Nii, Takahiro; Bungo, Takashi; Isobe, Naoki; Yoshimura, Yukinori (Frontiers in Physiology, 2021)
Intestinal environments such as microbiota, mucosal barrier function, and cytokine production affect egg production in laying hens. Dextran sodium sulfate (DSS) is an agent that disrupts the intestinal environment. Previously, we reported that the oral administration of dextran sodium sulfate (DSS: 0.9 g/kg BW) for five days caused severe intestinal inflammation in laying hens. However, the DSS concentration in the previous study was much higher to induce a milder disruption of the intestinal environment without heavy symptoms. Thus, the goal of this study was to determine the effects of a lower dose of DSS on the intestinal environment and egg production in laying hens. White Leghorn laying hens (330-day old) were oral administered with or without 0.225 g DSS/kg BW for 28 days (DSS and control group: n = 7 and 8, respectively). Weekly we collected all laid eggs and blood plasma samples. Intestinal tissues, liver, ovarian follicles, and the anterior pituitary gland were collected one day after the final treatment. Lower concentrations of orally administered DSS caused [1] a decrease in the ratio of villus height/crypt depth, occludin gene expressions in large intestine and cecal microbiota diversity, [2] a decrease in egg yolk weight, [3] an increase in VLDLy in blood plasma, [4] and enhanced the egg yolk precursor accumulation in the gene expression pattern in the follicular granulosa layer, [5] an increase in FSH and IL-1β gene expression in the pituitary gland and [6] an increase in concentration of plasma lipopolysaccharide binding protein. These results suggested that the administration of the lower concentration of DSS caused a slight disruption in the intestinal environment. This disruption included poor intestinal morphology and decreased cecal microbiome diversity. The change in the intestinal environment decreases egg yolk size without decreasing the VLDLy supply from the liver. The decrease in egg yolk size is likely to be caused by the dysfunction of egg-yolk precursor uptake in ovarian follicles. In conclusion, the oral administration of a lower dose of DSS is an useful method to cause slight disruptions of intestinal environment, and the intestinal condition decreases egg yolk size through disfunction of ovarian follicle.